Sequence and Apoptotic Activity of VacA Cytotoxin Cloned from a Helicobacter pylori Thai Clinical Isolate. (2nd April 2014) - Junaid, Muhammad; Al-Gubare, Sarbast; Yousef, Muhammad; Na Ubol, Mathukorn; Leetachewa, Somphob; Muanprasat, Chatchai; Angsuthanasombat, Chanan; Chaicumpa, Wanpen; Ali, Niaz; Katzenmeier, Gerd
Abstract : The vacuolating cytotoxin VacA produced by Helicobacter pylori induces the formation of large cytoplasmic vacuoles in host gastric epithelial cells as well as a release of cytochrome C from mitochondria resulting in cell apoptosis. Considerable sequence diversity in VacA relating to different degrees of disease severity is observed with clinical samples from a multitude of geographic places. In this study we describe expression in Escherichia coli, purification to homogeneity and in vitro assay of its apoptotic activity of a VacA toxin from a H. pylori isolate of a Thai patient with gastrointestinal lymphoma. Sequencing revealed that the deduced amino acid sequence of the cloned Thai isolate VacA is similar to H. pylori s1/m2 type strains. The percent sequence similarity to the model strain 60190 was lower due to the presence of extra amino acids in the mid (m) region. The purified VacA toxin exhibited significant apoptotic activity on both T84 and MDCK epithelial cell lines, as revealed by DAPI staining, whereby the observed activity was significantly higher on MDCK cells. These findings could relate to a modulation of VacA activity on host cells in the Thai isolate-VacA toxin that may differ from those of the model strain.